The Effectiveness of Emotion Regulation Therapy on Cognitive Disturbance, Function, and Difficulty in Emotion Regulation among Adolescents - Alimehdi, Mansour; Mohammdinia, Zahra (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Due to the high prevalence of emotional and cognitive problems among adolescents, paying attention to the emotional and cognitive problems of this population seems to be a necessity of society. Lack of paying attention to these problems leads to the persistence of these disorders in adulthood, therefore, the present study was conducted to evaluate the effectiveness of ERT based on the Gross model on adolescents. Materials and Methods:This study was a quasi-experimental research design involving 30 adolescents suffering from emotional problems. The used instruments included questionnaires of difficulty in emotion regulation, cognitive disturbance, and the Tower of London test. The assessment was performed in two stages including pre-test and post-test. SPSS-24 and one-way analysis of covariance were used to analyze the data. Results:The results of one-way analysis of covariance showed that ERT was able to significantly improve the target variables of difficulty in emotion regulation, cognitive disturbance, and the Tower of London test. Conclusion:It seems that using ERT based on the Gross model can improve the emotional problems of adolescents and prevent the occurrence of these problems among these people in adulthood.